No enhanced (p-) α-synuclein deposition in gastrointestinal tissue of Parkinson's disease patients. (November 2020) - Harapan, Biyan Nathanael; Frydrychowicz, Clara; Classen, Joseph; Wittekind, Christian; Gradistanac, Tanja; Rumpf, Jost-Julian; Mueller, Wolf
Abstract: Background: Neuronal alpha-synuclein (α-Syn) aggregation in the brain is believed to be a central component of the pathogenesis of Parkinson's disease (PD). α-Syn aggregates in the gastrointestinal tract have been suggested as a potential biomarker of PD that may even signal an early event of the Parkinsonian molecular pathology. However, studies further investigating this hypothesis have produced mixed results. Objective: To determine whether the prevalence of α-Syn- and serine 129-phosphorylated α-Syn (Ser129p-α-Syn) depositions detected in intestine from PD patients differed from that of non-Parkinsonian controls. Methods: In this retrospective study, we examined post-mortem small and large intestine samples of 25 PD patients and 20 age- and sex-matched controls without PD. Specimens were taken from archived paraffin-embedded tissue blocks. Immunohistochemical techniques were applied to detect α-Syn and Ser129p-α-Syn aggregates in situ. Immunoreactivity was quantified by a new approach that employed the detailed assessment of α-Syn- and Ser129p-α-Syn-positive morphological structures of the enteric nervous system (i.e., nerve fibers, myenteric and submucous plexus as well as ganglion cells). Results: α-Syn immunoreactivity was a common finding in intestinal tissues from PD patients and controls. Importantly, α-Syn and Ser129p-α-Syn immunoreactivity were significantly reduced in PD patients compared to controls in each of the morphological structures examined. Conclusions: Immunohistochemical detection of intestinal α-Syn and Ser129p-α-Syn seems to be a frequent and potentially normal finding. Neither α-Syn nor Ser129p-α-Syn immunoreactivity may, therefore, be regarded as a molecular intestinal biomarker of PD pathology. Reduced intestinal α-Syn and Ser129p-α-Syn immunoreactivity in PD patients rather reflect PD-related neuronal degeneration. Highlights: Largest postmortem study to date investigating α-Syn in gastrointestinal (GI) samples of Parkinson's disease (PD) patients. GI samples of healthy controls were frequently positive for (p-) α-Syn thereby questioning its role as a biomarker for PD. Both α-Syn and p-α-Syn immunoreactivity were significantly reduced in GI samples of Parkinson's disease patients. Reduced gastrointestinal (p-)α-Syn immunoreactivity in Parkinson's disease may reflect PD-related neurodegeneration.